Barriers and Facilitators that Influence on Adopting Healthy Lifestyles in People with Cardiovascular Disease - Jessica Natalia Saavedra Espinosa; Martha Yelitza Rodríguez Malagón; Sara Pamela Londoño Granados; Oscar Stiven Alméziga Clavijo; María Camila Garzón Herrera; Luz Patricia Díaz-Heredia (Universidad de Antioquia, 2021)
Objective. To measure lifestyle changes and describe the barriers and facilitators perceived that influence on adopting healthy lifestyles in people with cardiovascular diseases. Methods. Mixed study of concurrent execution in the public health center of the municipality of Tausa, Colombia. The quantitative phase corresponded to a longitudinal analytical method in which the FANTASTICO instrument was applied to 28 patients in this program between 0 and 120 days after a brief nursing intervention (face-to-face meetings and telephone calls). The qualitative phase was carried out with a micro-ethnographic approach applying a semi-structured interview to 12 out of 28 participants, 120 days after the intervention. Results. During the quantitative phase, a statistically significant change (p < 0.05) was the improvement of the total score and in the domains of activity, type of personality and insight between day 0 and 120. During the qualitative phase, 13 categories arose regarding barriers and facilitators to adopt a healthy lifestyle: four facilitators and one barrier for physical activity, three facilitators and three barriers for feeding, and two facilitators for stress management. By integrating the results, it is possible to explain that, for the change in eating behaviors, physical activity and stress management, personal biological and psychological factors, interpersonal and situational influences coincide with the assumptions and propositions of the Health Promotion Model by Nola Pender. Conclusion. The participants' lifestyles changed positively in three of the domains and the total of the instrument, which can be explained by simultaneous triangulation, by the facilitators and perceived barriers as influential on adopting behaviors to acquire a healthy lifestyle.